Implementasi Kebijakan Politik Hukum Dalam Penguatan Sistem Peradilan Di Indonesia - Ali, Bisyru Maulana; Muntazah, Afwah; Rahmawati, Nadya Riyanti; Sugianto, Sugianto; Tarmudi, Tarmudi (Hutanasyah : Jurnal Hukum Tata Negara, 2025)
This article examines the implementation of legal political policies in strengthening the justice system in Indonesia as a central issue in efforts to realize justice and legal certainty. This research aims to analyze the extent to which legal political policies have contributed to strengthening the justice system in Indonesia. The research method used is a literature study with a focus on statutory regulations, previous research results, and reports from related institutions. The research results show that legal political policies have had a significant impact in strengthening the justice system, but there are still a number of challenges that need to be overcome. Several policies that have succeeded in improving the quality of justice include criminal law reform, increasing access to justice, and strengthening judicial institutions. However, there are still a number of obstacles such as weak law enforcement, corruption, and a lack of public legal awareness. For this reason, continuous efforts are needed from various parties, including the government, judicial institutions and society, to continue to improve and strengthen the justice system in Indonesia. The analysis covers institutional, regulatory, human resources and judicial infrastructure aspects.